Thermal Environment for the Lunar Volatile Prospector Mission - Killian, Matthias; Fisackerly, Richard (47th International Conference on Environmental Systems, 2017)
Matthias Killian, Technical University of Munich, Germany Richard Fisackerly, European Space Agency (ESA), Netherlands ICES102: Thermal Control for Planetary and Small Body Surface Missions The 47th International Conference on Environmental Systems was held in South Carolina, USA on 16 July 2017 through 20 July 2017. The ESA mission concept Lunar Volatiles Prospector intends to send a rover to the south pole of the Moon for scientific exploration. Investigation of permanently shadowed regions (PSR) is one of the main objectives of the mission in the search for and analysis of volatiles. An instrument onboard a rover with a mobile range of about 50 km shall determine the distribution of water and other volatiles on a local scale. Previous analyses, which considered additional requirements on waypoints and scientific return, revealed a preference for the Shoemaker and Faustini crater region. On addition to mission constraints such as visibility to earth for communication purposes, available light for recharging batteries etc., the thermal environment plays a significant role for the success of a mission to this region. Lunar surface temperatures in the polar region vary between 25 K and 300 K for the targeted period in the year 2022. In this paper, a traverse is characterized regarding the thermal environment and corresponding heat fluxes of the rover. ESATAN-TMS was used in order to calculate radiative heat transfer and to solve the model. With analyses from this paper, dynamic thermal requirements can be established for a potential rover. In addition, thermal calculations from this paper shall be the baseline for future optimization of the traverse together with scientific requirements for a best scientific return as well as mitigating requirements for the design of the rover.